Zein-based nanoformulations with encapsulated methyl salicylate incorporated in 3D printing biopolymer devices targeting potential uses in pest management - Villarreal, Gabriela Patricia Unigarro [UNESP]; Santo Pereira, Anderson do Espirito [UNESP]; Matos de Freitas, Roberta Ranielle [UNESP]; Moraes, Maria Carolina Blassioli; Sepulveda, Anderson Ferreira; de Araujo, Daniele Ribeiro; Fraceto, Leonardo Fernandes [UNESP] (Elsevier, 2023)
The management of pests in agriculture has numerous issues, for instance, their impact in the environment. The use of synthetic semiochemicals for the pest control have a limited shelf life and low stability in the field. In this regard, nanocarrier systems may improve the stability overtime and to promote a sustainability release. The objective of this study was to prepare and characterized zein nanoparticles (NP-Zein) containing the semiochemical methyl salicylate (S_Met) and incorporated into sodium alginate (SA) and carboxymethyl cellulose (CMC)-created by 3D printing prototypes targeting as a potential application for pest management. The system was characterized using different physicochemical techniques and the results showed that the nanocarrier system had encapsulation efficiency of 99 % of S_Met. The NP-Zein had an average diameter of 150 nm with a polydispersity index of 0.18 ± 0.04. The incorporation of NP-Zein loaded S_Met in the crosslinked prototypes exhibited a rough surface with excellent NP-Zein adhesion as showed by fluorescence optical microscopy and atomic force microscopy images. The non-crosslinked prototypes had smooth and cracked surfaces, however, it did not affect the adhesion of NP-Zein loaded S_Met. Moreover, NP-Zein loaded S_Met in SA promote a sustained release over time, improving the S_Met stability and loss by volatilization. The results demonstrated that is possible to develop prototypes containing NP-Zein loaded S_Met by 3D printing using biodegradable polymeric materials. The developed prototypes can be a potential alternative for sustainable management aiming future application for pest control.
Keywords: Agriculture; Methyl salicylate; Nanotechnology; Printing biopolymer; Sodium alginate; Zein